The Influence of Transformational Leadership Ethics, Inclusive Education and Work Commitment on Teacher Loyalty Models in Senior High Schools in Tomohon City - Bernadina Waha Labuan; Jeffry S.J. Lengkong; Joulanda A.M. Rawis; Ruth Umbase (International Journal of Information Technology and Education, 2026)
Education was the main pillar in building quality human resources, both intellectually, morally, and socially. As a strategic investment, education plays a role in producing individuals who were able to face global challenges and contribute to the progress of society. The objectives of this study were; To determine the influence of Transformational Leadership Ethics on the Teacher Loyalty Model in Tomohon City Senior High Schools. To determine the influence of Inclusive Education on the Teacher Loyalty Model in Tomohon City Senior High Schools. To determine the influence of Work Commitment on the Teacher Loyalty Model in Tomohon City Senior High Schools. To determine the influence of Transformational Leadership Ethics, Inclusive Education and Work Commitment on the Teacher Loyalty Model in Tomohon City Senior High Schools. This study used a causality research design. Causal research design was used to prove the relationship between cause and effect of several variables. Causal research usually uses an experimental method, namely by controlling independent variables that would affect the dependent variable in a planned situation. For the Transformational Leadership Ethics variable, the dimension with the strongest influence was the idealized influence dimension on the rational dimension in the Teacher Loyalty Model, because it had a coefficient value = 0.646. For the Inclusive Education variable, the dimension with the strongest influence was the Accessibility dimension on the emotional dimension in the Teacher Loyalty Model, because it had a coefficient value = 0.861. For the Work Commitment variable, the dimension with the strongest influence was Continuance Commitment on the personality dimension in the Teacher Loyalty Model, because it has a coefficient value = 1.000. Based on the results above, it could be concluded; Transformational leadership ethics had a positive and significant influence on the teacher loyalty model. Inclusive education had a positive and significant influence on teacher loyalty. Work commitment had a positive and significant influence on the teacher loyalty model